An integrative view on the carotid artery alterations in metabolic syndrome - Wang, Zhi-Hao; Gong, Hui-Ping; Shang, Yuan-Yuan; Tang, Meng-Xiong; Fang, Ning-Ning; Jiang, Gui-Hua; Zhang, Yun; Zhong, Ming; Zhang, Wei (European journal of clinical investigation, 2012)
Eur J Clin Invest 2012; 42 (5): 496–502 Backgrounds  Metabolic syndrome (MetS) is a multiple risk factor paradigm widely considered in risk management. We aimed to investigate carotid artery alterations in MetS and the underlying risk factors. Materials and methods  A total of 400 Chinese subjects were recruited, divided into control (n = 200) and MetS (n = 200) groups. Clinical and laboratory characteristics were collected. All subjects underwent carotid ultrasonography. Results  Cardiovascular risk profiles were worse in the MetS than control group (all P < 0·05). After adjusting for MetS and age, the MetS group showed significantly increased mean intima‐media thickness (IMTmean) and significantly impaired carotid elastic properties (all P < 0·05), as compared to control group. Waist circumference (WC) was positively correlated with IMTmean (r = 0·130, P = 0·038), systolic carotid diameter (r = 0·139, P = 0·026) and diastolic carotid diameter (r = 0·168, P = 0·007). systolic blood pressure (SBP) and diastolic blood pressure were positively correlated with IMTmean (r = 0·201, P = 0·004; r = 0·168, P = 0·008, respectively), but negatively with arterial compliance coefficient (r = −0·421, P < 0·001; r = −0·230, P < 0·001, respectively). Serum level of high‐density lipoprotein (HDL) negatively correlated with IMTmean (r = −0·195, P = 0·002). Plaque index was positively correlated with fasting blood glucose (r = 0·205, P = 0·001) after adjusting for the other risk factors. Significantly impaired carotid elastic properties (all P < 0·05) independently correlated with IMTmean. Furthermore, age (β = 0·255, P < 0·001), SBP (β = 0·224, P < 0·001), WC (β = 0·202, P < 0·001) and high‐density lipoprotein cholesterol (HDL‐C) (β = −0·163, P = 0·001) were independently associated with IMTmean. Conclusion  Carotid alterations consequent upon MetS ultimately developed subclinical and clinical atherosclerosis, the underlying risk factors for which were abdominal obesity, hypertension, ageing and low level of HDL‐C.